An Overview of Optimal Input-Output Planning Model and Cross-Boundary Economic Management Information System — Real-time Analysis of Input-output Optimal Planning Models and Timely Analysis of Input-output Statistical Models - Kang, Ning (New Innovations in Economics, Business and Management Vol. 8, 2022)
Cross-boundary, which is the key word of IT industry in 2010, swept down from upstream industries to downstream terminals, PC, software, internet… no exception in all areas. With the combination of mobile and internet, a revolutionary change has been brought about. However, the power of traditional fields can never remain mighty in new areas. By using mathematical tools form the thinking mode of discrete mathematics and continuous mathematics, the second cross-boundary is a theoretical basis of cross-boundary economic management information system as well as a scientific method for realising the integration between the optimal input-output planning model and Big data, new technologies of Cloud Computing and Internet of Things or new internet industry. With the second cross-boundary, area, scale, strength and efficiency of its application will be beyond our imagination. Based on modernisation of enterprise management, the cross-boundary economic management information system can be used to promote not only management of enterprises, but comprehensively enhance modern management quality and governance capacity. It is not only a scientific basis for establishing “One World”, justice, mutual benefit and equal competition, it is also a method to completely eradicate the breeding ground of waste and corruption. In this paper, a brief description will be given based on real-time analysis of the optimal input-output planning model and timely analysis of input-output statistical model. Note: For convenience, the shorter forms which are mentioned in this paper: cross-boundary economic management information system, short for the optimal input-output planning model and cross-boundary economic management information system; input-output model, short for input-output planning model and input-output statistical model; the optimal input-output planning model, short for the optimal micro input-output planning model and the optimal macro input-output planning model; input-output statistical model, short for micro input-output statistical model and macro input-output statistical model; real-time analysis of the optimal micro input-output planning model, short for real-time analysis of the optimal micro input-output planning model and timely analysis of micro input-output statistical model; real-time analysis of the optimal macro input-output planning model, short for real-time analysis of the optimal macro input-output planning model and timely analysis of macro input-output statistical model; real-time analysis of the optimal input-output planning model and timely analysis of input-output statistical model, short for real-time analysis of the optimal micro input-output planning model and timely analysis of micro input-output statistical model as well as real-time analysis of the optimal macro input-output planning model and timely analysis of macro input-output statistical model; combinations and connections between the optimal macro input-output planning model and the optimal micro input-output planning model, short for combinations and connections between the optimal macro input-output planning model and the optimal micro input-output planning model as well as macro input-output statistics model and micro input-output statistics model; new technology, short for Big data and new Cloud Computing technologies; new industry, short for Internet of Things or new internet industry; combinations between the optimal input-output planning model and new technology and new industry, short for combinations of the optimal micro input-output planning model and new technology and new industry as well as the optimal macro input-output planning model and “new technology” and “new industry”; engineering design is referred to product structure design and process design; manufacturing is referred to combinations of these three elements: objects of labor, labor force, means of labor and relevant progresses; operation management is referred to market management and finance management.